Cyber paranormal : conflict of law issues in E-Commerce consumer contracts / Sheela Jayabalan - Jayabalan, Sheela (Universiti Teknologi MARA, Shah Alam, 2014)
The advancement of information and communication technology (ICT) has taken commerce to a trans border or cross border heights which sees no boundaries on the globe. In an ecommerce transaction via the Internet, a consumer located in Malaysia can browse the World Wide Web and purchase goods from any part of the world with the click of the mouse. Cross- border transactions used to be the concern of big enterprises and wholesalers. The Internet has transformed this fact with thousands of consumer contracts or business to consumer contracts (B2C) being made every day with suppliers and purchasers almost inevitably situated in different parts of the world. The interconnectivity nature of the Internet dismembers the borders of the globe. Traditional norms to assert jurisdiction in the instance of a breach of a contract such as, the place where the contract was made or the place of performance of the contract or the domicile of the contracting parties have become meaningless. Is the Internet which is known as the cyberspace really a place without borders and beyond the reach of laws? Because, a legal system is confined to its territory. Whereas, the infrastructure of the Internet sees no border. Question arises as to; how is the law of a state to apply when Internet penetration is not confined to one jurisdiction but penetrates into multitude of jurisdiction? Thus, the aim of this article is to highlight the conflict of law issues that the Internet gives rise to consumer contracting for the sale of goods via the Internet in the Malaysian perspective. Is the conflict of laws principles or private international law in Malaysia equipped to deal with cross border transactions for the sale of goods via the Internet? Does the conflict of laws in Malaysia give any significance to consumer transactions?